Prevalence of Neisseria gonorrhoeae and Chlamydia trachomatis in men having sex with men in Port-au-Prince, Haiti: a cross-sectional study - Frantz Jean Louis; Josiane Buteau; Jacques Boncy; Jean Wysler Domercant; Guethina Galbaud; Maureen Leonard; Emmanuel Pericles; Ito Journel; Regine Jean Francois (BMJ Open, 2020)
Objectives Over the last 15 years, the prevalence of HIV in Haiti has stabilised to around 2.0%. However, key populations remain at higher risk of contracting HIV and other sexually transmitted infections (STIs). The prevalence of HIV is 12.9% among men having sex with men (MSM). There is limited information about the prevalence of other STI in the Haitian population in general and even less among key populations. We assessed the burden of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) and risk factors for infections among MSM in Haiti.Methods A cross-sectional study was conducted. MSM were recruited from seven health facilities in Port-au-Prince. All samples were tested by nucleic acid amplification test, using GeneXpert. A survey was administered to the participants to collect socio-demographic, clinical and risk behaviour data.Results A total of 216 MSM were recruited in the study. The prevalence rates of CT and NG were 11.1% and 16.2%, respectively. CT NG co-infections were found in 10/216 (4.6%) of the participants. There were 39 MSM with rectal STI compared with 17 with genital infections. Participants between 18–24 and 30–34 years old were significantly more likely to be infected with NG than those aged 35 years or older (OR: 22.96, 95% CI: 2.79 to 188.5; OR: 15.1, 95% CI: 1.68 to 135.4, respectively). Participants who never attended school or had some primary education were significantly more likely to be infected with NG than those with secondary education or higher (OR: 3.38, 95% CI: 1.26 to 9.07). People tested negative for HIV were significantly more likely to be infected with CT than people living with HIV/AIDS (OR: 3.91, 95% CI: 1.37 to 11.2).Conclusions Periodic risk assessment and testing for STI should be offered in Haiti as part of a comprehensive strategy to improve the sexual health of key populations.